Mechanistic insights of magnolol antimicrobial activity against Mycoplasma using untargeted metabolomic analyses - Qiao, Hu; Tengfei, Zhang; Wenting, Zhang; Qin, Lu; Yunqing, Guo; Xiaoyi, Cao; Huabin, Shao; Xinguo, Zhai; Qingping, Luo (Frontiers in Cellular and Infection Microbiology, 2023)
The unreasonable use of antibiotics is one of the important causes of antimicrobial resistance (AMR) that poses a huge public health threat. Magnolol is a traditional Chinese medicine exhibiting antibacterial-, antifungal-, anti-inflammatory-, and antioxidant activities. However, it is unclear whether magnolol has an inhibitory effect on mycoplasma. This study found that magnolol showed excellent inhibitory activity against various mycoplasmas. Magnolol showed dose-dependent inhibition of Mycoplasma synoviae growth and biofilm formation in vitro. Magnolol caused severely sunken and wrinkled M. synoviae cell membranes at the minimum inhibitory concentration, and an enlarged cell diameter. The chicken embryo infection model showed that magnolol significantly reduced M. synoviae pathogenicity in vivo. Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that the citrate cycle, glycolysis/gluconeogenesis, and pyruvate metabolism were significantly disturbed at the minimum inhibitory concentration of magnolol. Interestingly, 41% of differential metabolites were in the categories of lipids and lipid-like molecules. Protegenin A was up-regulated 58752-fold after magnolol treatment. It belongs to fatty acyls, and destroys cell membrane integrity and cell activity. Ghosphatidylethanolamine, phosphatidylglycerol, phosphatidic acid, and phosphatidylserine related to membrane maintenance and stress response were widely down-regulated. Collectively, our results illustrate the feasibility of magnolol as a phytochemical compound to treat mycoplasma infection.